The effects of fighting populism on the populist dynamic - Vincenzo Galasso (EconPol Forum, 2024)
Populism is on the rise globally and poses an existential threat to mainstream political parties. Traditional parties may try to debunk the populist rhetoric or fight back using populist tactics. A field experiment during the 2020 referendum in Italy shows that fighting back may be effective. Political ads blaming populist politicians demobilized their electoral base at low economic cost. Fighting populists backfires in the medium term as new populists benefit from the increased abstention.
Keywords: 330